Entre Oriente y Occidente. La relectura de los mitos en la obra traducida de Joumana Haddad (ENTHYMEMA, 2020)
Contemporary mythology - created in recent centuries or the outcome of a reinterpretation of classical myths in the present - is conditioned by the language and culture in which it is developed and embraced. This becomes more acute when there is an exchange of myths between East and West. Then the translation acts as a fundamental element in the transmission. Furthermore, translation involves a tension between meanings in the original and the final language, which is very complex when different cultures are involved. According to these approaches, current revisions of myths produced in the literature of the Arab world that have arrived at the western reader, and specifically at the Spanish language one, are studied.  Specifically, it deals with the reinterpretation and rupture of the myth of Superman by the writer Joumana Haddad (Beirut, 1970) through the application of the features of this figure to the current Arab man.
Keywords: Contemporary mythology; reinterpretation; Arab literature